Guided image completion by confidence propagation. (February 2016) - Tan, Xiao; Sun, Changming; Wong, Kwan-Yee K.; Pham, Tuan D.
Abstract: This paper presents a new guided image completion method which fills any missing values by considering information from a guidance image. We develop a confidence propagation scheme that allows the filling process to be carried out simultaneously without the need of deciding the filling order. We conduct experiments in several applications where the problem can be formulated into a guided image completion problem, such as interactive segmentation and colorization. The experimental results show that our method provides good results and succeeds in situations where conventional methods fail. In addition, as all building blocks are parallel processes, our method is much suitable for hardware acceleration. Abstract : Highlights: We proposed an image completion method based on a new formulation. Filling process was carried out simultaneously without deciding the filling order. Good results were obtained in a variety of applications.